Cancer Care in Pakistan: A Descriptive Case Study. (12th January 2022) - Rattani, Salma A; Dahlke, Sherry; Cameron, Brenda
In this descriptive case study, we aimed to understand the experiences of cancer diagnosis, treatment, and palliative care in Pakistan. The case was limited to a hospital for cancer and hospice care in Karachi, Pakistan. Data collection included interviews with patients who had a cancer diagnosis, family members, healthcare providers, and unstructured observations. Two themes of suffering and late diagnosis were developed to describe the experiences of people with cancer. Suffering occurred as a result of poverty, social ideas about cancer, and physical suffering. Late diagnosis happened because of cultural ideas about health, low health literacy, and healthcare challenges, although both themes are interconnected. The findings illuminate three key pathways that will improve cancer diagnosis and palliative care in Pakistan: specifically, the need to (a) educate healthcare providers about cancer and palliative care, (b) eradicate corruption in healthcare, and (c) develop policies for universal access to health.